Perception of quality of life in Brno housing estates - Andráško, Ivan; Lesová, Pavlína; Kunc, Josef; Tonev, Petr (Hungarian Geographical Bulletin, 2013)
The main goal of this paper is to introduce and discuss the ways of perceiving the quality of life on selected housing estates of Brno City. At a general level we focus on the significance of this kind of research and the factors infl uencing the way housing estates and living there are perceived in the Czech Republic. The results of our research on three Brno housing estates imply that the "external" image of quality of life on a housing estate can be rather different from the feelings and opinions of inhabitants living there. That contradiction is a result of a quite wide spectrum of factors such as adaptation processes, local patriotism or media influence.